Approach to the funeral march Duelo de la Patria by Rafael Chávez Torres - Meza Sandoval, Gerardo E. (2024)
The shared approach in this essay appeared in search of answers to questions about the most beloved funeral march in Costa Rica. Thosequestions were generated after reading the book on Rafael Chávez Torres by the researcher Ligia María Rosales Chacón. Some elements of Julia Kristeva about text theory are used, bringing us closer to thepyramidal structure of the sign ideologeme, from which we analyze the president of Costa Rica Tomás Guardia, we make a reading of the androcentric concept that he represents, and we approach it to concepts such as tonality. As music is a social text, we reviewed the musicaldrama using elements of the Western musical tradition, for which wepresented some musical signs and highlighted those that we consider reasons for pain that are used in the musical piece.